Javanese Silly Gags on Daily Communication on Social Media: Pragmatic Meanings and Functions Approach - Rahardi, R. Kunjana; Handoko, Handoko; Rahmat, Wahyudi; Setyaningsih, Yuliana (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
This qualitative descriptive study aims to explore the pragmatic significance of rarely researched Javanese silly gags. The primary objective is to examine the markers and implications of these gags in daily communication, particularly focusing on their various categories. Utilizing social media fragments as the primary source, the research employs the note-taking method for listening. Subsequent steps include the identification, classification, and characterization of Javanese silly gags into five distinct categories: (1) Silly jokes for enthusiasm, (2) Silly jokes for sarcasm, (3) Silly jokes for satire, (4) Silly jokes for exasperation, and (5) Silly jokes for enigmatic humor. The equivalent analysis method is then applied, specifically using contextual equivalents through a comparative linking technique for in-depth data analysis. The emphasis on context is considered a crucial factor in conducting purpose-oriented pragmatic studies. The analysis reveals valuable insights into the diverse functions of Javanese silly gags, showcasing their significance in daily communication. The identified categories provide a comprehensive understanding of how these gags serve various purposes, from expressing enthusiasm to conveying sarcasm, satire, exasperation, and enigmatic humor. The social media fragments prove to be rich sources for uncovering the nuances of Javanese silly gags and their markers. The findings of this study shed light on the multifaceted nature of Javanese silly gags, highlighting their importance in preserving a unique form of humor. The study emphasizes the potential threat posed by the younger generation’s lack of comprehension. It underscores the need to preserve and understand Javanese silly gags in the evolving landscape of communication. Overall, this research contributes to the broader understanding of pragmatic aspects in Javanese humor, emphasizing the cultural and communicative significance of these often-overlooked forms of expression.